Morphometric Study Of Placenta And Its Correlation In Normal And Hypertensive Pregnancies. - PRADEEP S LONDHE,; ABHAY B MANE, (International Journal of Pharma and Bio Sciences, 2011)
Placenta is a vital organ for maintaining pregnancy and promoting normal foetal development. Foetal outcome is adversely influenced by pathological changes observed in placenta. Pregnancy complications like hypertension are reflected in placenta. The objective was to assess the morphology of placenta in normotensive and hypertensive pregnancies and to correlate the morphometric analysis with fetal parameters between the two groups. A Cross-sectional descriptive study was undertaken in the Department of Anatomy, Chalmeda Anandrao Institute of Medical Sciences, Karimnagar, Andhra Pradesh. Total 300 human placentae, 150 from hypertensive pregnancies were studied for the morphology and compared with 150 placentae from normal pregnancies. The morphometric parameters of placenta like weight, volume were significantly lower in hypertensive group compared to normal group. Placental weight and placental volume had significant correlation with the birth weight of new born. Pregnancy induced hypertension is associated with substantial changes in placental morphology due to reduced uteroplacental blood flow.